Pengaruh Komite Audir, Kompleksitas Perusahaan Dan Ukuran Perusahaan Terhadap Audit Delay - Dewantomo Dewantomo; Nurma Gupita Dewi (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The aim of this research is to empirically prove the influence of the audit committee, company complexity and company size on audit delay. The population in the research is all food and beverage companies listed on the Indonesia Stock Exchange 2020-2022. The sample selection method chosen was the purposive sampling method so that 78 observations were obtained. The data analysis technique used is multiple linear regression analysis using the SPSS application. The research results show that the audit committee and company complexity have a significant positive effect on audit delay, while company size has a significant negative effect on audit delay.